Eksplorasi Komposit Sandwich Berbasis Polyurethane sebagai Alternatif Material Struktural dalam Industri Kelautan - R. Puranggo Ganjar Widityo Widityo; Sumarji; Dani Hari Tunggal Prasetiyo; Subhannaan Alif Rezeki (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The use of lightweight structural materials, high mechanical strength, and resistance to corrosive marine conditions is very important for the marine industry. The properties of lightweight, strong, and corrosion-resistant materials can be fulfilled by one of the materials, namely polyurethane sandwich composites. The purpose of this study is to study how sandwich composites function mechanically with various types of reinforcing layers (skins), including Chop Strand Mat (CSM), Woven Roving (WR), and a mixture (CSM + WR) and two types of cores, namely polyurethane sheet and polyurethane foam. This study uses a hand lay-up technique to make sandwich composite specimens. Then, the specimens were tested with flexural and impact tests to measure the mechanical properties of the material. The flexural test results showed that the specimen with WR skin and polyurethane sheet core had the highest flexural strength of 94.78 MPa. On the other hand, the impact test, the WR composition also showed the best value, with an impact value of up to 0.34 J/mm² in the polyurethane foam core configuration. The results showed that the sandwich composite consisting of a WR skin and a polyurethane foam core had the best mechanical performance in terms of flexural strength and impact toughness. Therefore, this composite can be used as an alternative structural material in marine industry applications.